MMP9: Link between neuropathy and colorectal cancer? - Regalado, Cynthia Rosa; Balogh, Mihály (Frontiers in Molecular Biosciences, 2024)
As chemotherapy is still a cornerstone of colorectal cancer (CRC) treatment, chemotherapy-induced peripheral neuropathy (CIPN) presents significant clinical challenges, affecting millions worldwide. A subset of colon cancer patients (approximately 30%) develop chronic CIPN, with detrimental, untreatable neuropathic pain symptoms. The risk factors of such intractable chronic CIPN are unknown. However, there is growing literature data investigating the intriguing interplay of neurons and cancer (cancer neuroscience). Recent data shows that this interplay might have a key role in the development and severity of CIPN. Given its vast (patho)physiological roles in both colon cancer and neuropathy, MMP9 seems to be a key factor that might drive the development of neuronal damage in colon cancer patients. This review investigates the role of matrix metalloproteinase 9 (MMP9) in linking CRC to neuropathy, aiming to uncover shared mechanisms that could offer new therapeutic targets. By synthesizing insights from a broad range of studies published over the last 20 years, we explore MMP9’s involvement in CRC progression, its role in CIPN, and the interconnected pathways influencing both conditions. These studies reveal MMP9 as a pivotal mediator in ECM remodeling, inflammation, and signal transduction pathways, emphasizing its modulation by macrophages. These shared mechanisms of colon cancer and CIPN pathophysiology suggest MMP9’s potential contribution to neuropathic conditions in CRC patients, positioning it as a critical factor in disease progression and a promising therapeutic target. Future research should focus on longitudinal studies to assess MMP9’s impact on neuropathy outcomes in CRC patients, exploring MMP9 inhibitors, and developing targeted interventions to mitigate the detrimental symptoms of CIPN. MMP9 also seems to be a feasible driving factor in the development of chronic CIPN in colon cancer patients.